La resiliencia socio-económica y de salud en la población de la ciudad de Guaranda ante la huella de la pandemia del COVID – 19, en el periodo mayo-septiembre 2022 - Agualongo Arias, Karem Mishell (2022)
Within the etiology classification of disasters are those that derive from the effects on human health due to diseases that are acquired due to their rapid contagion and advance, which is why, as in the present case of COVID-19, the declaration occurs Consequently, this forced the majority of states to declare states of emergency and exception in their territories, which affected not only health but also the different educational, productive, commercial activities, etc., causing a negative impact on the societies of all the planet. The presence of this pandemic has left its mark not only in the economic aspects but above all in the human and social aspects, for which we proposed to carry out this case study work, in which the following objectives are established and achieved, such as: Carry out a diagnosis of the current situation of COVID 19 in the population of the city of Guaranda, in which it is possible to determine the situation of the Guaranda population, the main affectations that took place, is identified through the application of tools of information collection the real perception of the people who carry out private economic activities since this private sector is the one that was most affected in social and economic aspects. It is possible to define the resilience capacity of the population in the city of Guaranda in the face of a threat with information provided by the identified actors and who were part of this COVID 19 work, and then as a third objective to carry out the proposal of strategies to strengthen the resilience of the population in the city of Guaranda in the face of COVID 19, we as students of the Disaster Administration and Risk Management Career hope that the authorities take into consideration to put it into execution, for which a qualitative investigation is applied, with collection of documentary information and interviews with the inhabitants of the city of Guaranda, especially those who have an economic activity with.